Synchronous Fluorescence Determination of Streptomycin in Biological Fluids with CdTe/CdSe Quantum Dots as Fluorescence Probe - Mao, Yongqiang; Li, Na; Han, Ye; Liu, Nan; Gao, Zhixian; Zhou, Zhijiang (Asian Journal of Chemistry, 2012)
A simple, rapid and sensitive synchronous fluorescence method was developed for the determination of streptomycin in biological fluids. When trace amounts of streptomycin was added into the CdTe/CdSe core/shell quantum dots solution, the synchronous fluorescence intensity of the system was significantly enhanced. With Dl = 230 nm, maximum synchronous fluorescence at pH 8.5 was generated at 345 nm. Under optimum conditions, a good linear relationship between the fluorescence intensity and the streptomycin concentration was obtained in the range from 1.0 to 10 μmol L-1 with a correlation coefficient of 0.9971. The corresponding detection limit was 25 nmol L-1 for streptomycin. Furthermore, some common metal ions, amino acids and some pharmaceuticals, which were regularly used together with streptomycin in medicine, did not interfere with the determination of streptomycin under general conditions. This method was successfully applied to determine streptomycin in human serum and urine samples and the satisfactory results were obtained. In addition, the possible mechanism of the fluorescence enhancement was also discussed.